2009
DOI: 10.1172/jci40572
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role for glycogen synthase kinase–3 in hematopoietic stem cell homeostasis in mice

Abstract: Hematopoietic stem cell (HSC) homeostasis depends on the balance between self renewal and lineage commitment, but what regulates this decision is not well understood. Using loss-of-function approaches in mice, we found that glycogen synthase kinase-3 (Gsk3) plays a pivotal role in controlling the decision between self renewal and differentiation of HSCs. Disruption of Gsk3 in BM transiently expanded phenotypic HSCs in a β-catenin-dependent manner, consistent with a role for Wnt signaling in HSC homeostasis. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 51 publications
5
120
0
1
Order By: Relevance
“…It has been shown that the absence of GSK3b impairs long-term self-renewal capacity of HSCs, although it is not essential for myeloid development (23). While HSCs from the triple cyclin knockout mouse (cyclins D1, D2, and D3) display delayed cell-cycle entry and multilineage hematopoietic failure (46,47), single knockouts for D1 or D2 display normal granulocyte counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the absence of GSK3b impairs long-term self-renewal capacity of HSCs, although it is not essential for myeloid development (23). While HSCs from the triple cyclin knockout mouse (cyclins D1, D2, and D3) display delayed cell-cycle entry and multilineage hematopoietic failure (46,47), single knockouts for D1 or D2 display normal granulocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 regulates HSC self-renewal and lineage commitment (23,24) and controls genes that are important for proliferation such as cyclin D1 (25) and D3 (26). Myeloid progenitor bone marrow cells from mice treated with G-CSF for 5 days and with genistein on the last 2 days of G-CSF treatment were sorted, lysed, and the proteins were analyzed by Western blot.…”
Section: Genistein Limits Dna Damage Through Inhibition Of Proliferationmentioning
confidence: 99%
“…However, there are conflicting reports on the requirement for Wnt/ -catenin signaling in basal hematopoiesis: conditional disruption of -catenin in adult HSCs does not affect their ability to self-renew and reconstitute hematopoietic lineages (Huang et al, 2009). In addition, although overexpression of stabilized -catenin increases immunophenotypic HSCs, this is associated with a loss of repopulating activity and hematopoietic failure in vivo (Kirstetter et al, 2006), findings that appear incompatible with a positive role for -catenin in hematopoiesis.…”
Section: Wnt Pathway and Hscmentioning
confidence: 99%
“…In a steady state, low levels of HSPCs are constantly circulating as part of homeostasis, whereas in stress situations, HSPCs are recruited in high numbers from the bone marrow (BM) into the circulation as part of host defense and repair mechanisms (2). Glycogen synthase kinase-3β (GSK3β) is a well-established negative regulator of the Wnt/β-catenin pathway, implicated in self-renewal and development of human and murine HSCs (3)(4)(5)(6)(7)(8)(9)(10)(11). In addition to proliferation, GSK3β has been shown to be involved in the motility of various cells, including microglia, epidermal stem cells, human mast cells, and breast cancer cells (12)(13)(14)(15)(16), but its effect on the motility of immature hematopoietic cells has not been addressed.…”
Section: Introductionmentioning
confidence: 99%